The Next Step in the Treatment of Stroke - Matei, Nathanael; Camara, Justin; Zhang, John H. (Frontiers in Neurology, 2021)
Although many patients do not receive reperfusion therapy because of delayed presentation and/or severity and location of infarct, new reperfusion approaches are expanding the window of intervention. Novel application of neuroprotective agents in combination with the latest methods of reperfusion provide a path to improved stroke intervention outcomes. We examine why neuroprotective agents have failed to translate to the clinic and provide suggestions for new approaches. New developments in recanalization therapy in combination with therapeutics evaluated in parallel animal models of disease will allow for novel, intra-arterial deployment of therapeutic agents over a vastly expanded therapeutic time window and with greater likelihood success. Although the field of neuronal, endothelial, and glial protective therapies has seen numerous large trials, the application of therapies in the context of newly developed reperfusion strategies is still in its infancy. Given modern imaging developments, evaluation of the penumbra will likely play a larger role in the evolving management of stroke. Increasingly more patients will be screened with neuroimaging to identify patients with adequate collateral blood supply allowing for delayed rescue of the penumbra. These patients will be ideal candidates for therapies such as reperfusion dependent therapeutic agents that pair optimally with cutting-edge reperfusion techniques.